The blind faith hotel - Todd, Pamela (Margaret K. McElderry Books, 2008)
When her parents separate and she and her siblings move with their mother from the northwest coast to a midwest prairie farmhouse, fourteen-year-old Zoe, miserably unhappy to be away from the ocean and her father, begins to develop a deep attachment to her new surroundings, when, after a shoplifting episode, she is assigned to work at a nature preserve.